Towards a cultural transition of energy landscapes – Between responsibility and necessity - Giorgio Peghin (Agathón)
Every transition introduces a moment of novelty; however, in the environmental and landscape field, the effects of this change can be critical for various reasons. The first reason relates to the impacts of industrial infrastructures, mobility and the management of environmental processes, and is related to the lack of cohesion between the structures and the landscape. A second issue relates to decision-making processes and the principle of accountability of the same especially in environmental matters. Finally, the third point involves the temporal dimension and, more generally, the design of time as a system of relationships. This contribution aims, therefore, to reflect on the role of architectural design in complex contexts, providing operational indications and establishing the need to ‘read’ the present world and interpret it critically, avoiding exclusive technocratic dominion in issues that affect the future of the next generations and the destinies of our landscape.